An Empirical Model for Predicting the Kinetics of Desorption of Ingredients from Polymeric Materials of Different Thickness. (April 2017) - Dedov, A.V.
The use of an empirical model for predicting the desorption kinetics of ingredients and impurities from polymeric materials is analysed. A shortcoming of the model considered is the dependence of the reduction factor on the thickness of the polymeric material, which limits the use of different data. An approach for solving this problem is proposed.